ANALISIS BREAK EVEN POINT (BEP) USAHATANI TOMAT DI DESA TARAITAK I KECAMATAN LANGOWAN KABUPATEN MINAHASA (BREAK EVEN POINT (BEP) ANALYSIS OF TOMATO FARMING BUSINESS IN TARAITAK I VILLAGE, LANGOWAN DISTRICT, MINAHASA DISTRICT) - Rizaldi ., Manono; Eyverson ., Ruauw; Mellisa Lady Gisela Tarore (AGRI-SOSIOEKONOMI, 2021)
The purpose of this study was to analyze the break even point or break even point of tomato farming in Taraitak Satu Village, Langowan Utara Districk. This study was conducted for 3 months by taking 20 respondents. This sampling process is conducted by simple random sampling. The results showed that at theÂ  prevailing price lvel and the proction result acheved, the tomato farmers in taraitak 1 village earned an income fo RP 1.942.822 in one planting. The break-even point (BEB value) of tomato farming in one planting in Taraitak 1 village is achieved at a value of IDR 1.055.181. The amount of production that must be obtained by tomato farmers in Taraitak 1 Village in order to break even is 179 kg at a price per kg level of IDR 5,893, and the price per kg of tomatoes that must be obtained by farmers in Taraitak 1 Village in order to break even is IDR 584 , or in other words, the minimum price for tomatoes in Taraitak 1 Village is IDR584 at a production level of 1.808 kg.